Rapid differentiation of isobaric and positional isomers of structurally related glycosides from Phytolacca bogotensis. (2009)
Through the action of glycosyltransferases, a plant can biosynthetically assemble small different aglycons or 'templates' to various polysaccharides to produce numerous glycoconjugates differing in the type of the attached aglycon, the anomeric configuration of C-1 of the glycosylating sugar, the type of sugar and the different position of attachments of the sugar unit present in the polysaccharide chain. The position of attachments and the anomeric configuration of the different sugar present in the polysaccharide create the opportunity to generate molecules with either the same or very close molecular weights, which have relative structural similarity--forming isobaric and positional isomers. Although isomeric differentiation was once considered outside of the domain of mass spectrometry, this task can now be resolved using tandem mass spectrometry. In a standardized purified glycoconjugate fraction (SPT01) from Phytolacca bogotensis, we report conventional electrospray ionization mass spectrometry and collision-induced dissociation (CID) MS/MS parameters which favored the formation of characteristic product ions. This allowed us to suggest the type of sugar linkages present in a specific glycoconjugate. Ten new glycoconjugate are described from this plant and another twelve known saponins were structurally characterized using the automatic MSn acquisition mode. The differentiation of two pairs of positional isomers and four isobaric glycosides and the production of a library of 30 glycosides present in P. bogotensis were accomplished.